Persistent Energetic Electrons in Methylammonium Lead Iodide Perovskite Thin Films - Niesner, Daniel; Zhu, Haiming; Miyata, Kiyoshi; Joshi, Prakriti P.; Evans, Tyler. J. S.; Kudisch, Bryan. J.; Trinh, M. Tuan; Marks, Manuel; Zhu, X. -Y. (Journal of the American Chemical Society, 2016)
In conventional semiconductor solar cells, carriers are extracted at the band edges and the excess electronic energy (E*) is lost as heat. If E* is harvested, power conversion efficiency can be as high as twice the Shockley-Queisser limit. To date, materials suitable for hot carrier solar cells have not been found due to efficient electron/optical-phonon scattering in most semiconductors, but our recent experiments revealed long-lived hot carriers in single-crystal hybrid lead bromide perovskites. Here we turn to polycrystalline methylammonium lead iodide perovskite, which has emerged as the material for highly efficient solar cells. We observe energetic electrons with excess energy < E*> approximate to 0.2S eV above the conduction band minimum and with lifetime as long as similar to 100 ps, which is 2-3 orders of magnitude longer than those in conventional semiconductors. The energetic carriers also give rise to hot fluorescence emission with pseudo-electronic temperatures as high as 1900 K. These findings point to a suppression of hot carrier scattering with optical phonons in methylammonium lead iodide perovskite. We address mechanistic origins of this suppression and, in particular, the correlation of this suppression with dynamic disorder. We discuss potential harvesting of energetic carriers for solar energy conversion.